Las medidas sanitarias y fitosanitarias en el Perú: marco teórico y legal - Zúñiga Schroder, Humberto (2022)
The increasing demand for food products whose consumption does not generate unfavourable effects on peoples’ health has led to a considerable growth in the number of sanitary and phytosanitary measures developed — and used— worldwide. However, this growth has not been accompanied, in many cases, by a general understanding of the role played by such measures in our economy, nor the legal framework within which these are framed. The present paper is focused on explaining the theoretical and legal framework related to the so-called sanitary and phytosanitary measures, as well as the advantages and potential impacts derived from their use.